2022
DOI: 10.30604/jika.v7i1.1319
|View full text |Cite
|
Sign up to set email alerts
|

Drug Inventory Management Using ABC-VEN and EOQ Analysis for Improving Hospital Efficiency

Abstract: Pharmaceutical Installation at Hospital is a service unit that has a very large influence on hospital services and income from hospitals because the source of income and expenses comes from pharmaceutical installation activities in procurement to distribution. This research is a study on inventory management for Pharmaceutical supplies at Santo Yusup Boro Kulon Progo Hospital, Yogyakarta, this study aims to find a suitable inventory management calculation method that can be applied in hospitals, researchers ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
0
0
1
Order By: Relevance
“…By maintaining an up-to-date and accurate record of the items and supplies, inventory management solutions inside large hospitals may assist in shielding their healthcare system from financial and product losses. Studies have revealed that fundamental quality control practices, consumer satisfaction, and waste removal are chances for improvement in healthcare centres of developing nations (Soraya et al, 2022) Utilizing inventory management software recently has helped the healthcare sector enhance the efficacy or efficiency within its distribution networks (Baloch & Rashid, 2022). The requirement for drugs and screening procedures tools is rising quickly in the healthcare sector.…”
Section: The Challenges Of Inventory Management In Medical Supply Cha...mentioning
confidence: 99%
“…By maintaining an up-to-date and accurate record of the items and supplies, inventory management solutions inside large hospitals may assist in shielding their healthcare system from financial and product losses. Studies have revealed that fundamental quality control practices, consumer satisfaction, and waste removal are chances for improvement in healthcare centres of developing nations (Soraya et al, 2022) Utilizing inventory management software recently has helped the healthcare sector enhance the efficacy or efficiency within its distribution networks (Baloch & Rashid, 2022). The requirement for drugs and screening procedures tools is rising quickly in the healthcare sector.…”
Section: The Challenges Of Inventory Management In Medical Supply Cha...mentioning
confidence: 99%
“…Berdasarkan hasil wawancara yang dilakukan oeh peneiti dengan salah satu pegawai rumah sakit tersebut terdapat beberapa permasalahan yang terjadi pada Rumah Sakit Umum Daerah (RSUD) dr.Djasamen Saragih Pematangsiantar misalnya, terjadi kehabisan stok obat yang dapat menyebabkan peayanan rumah sakit terhambat dan juga permasalahan keebihan stok obat yang dapat menyebabkan biaya persediaan yang meningkat. Keebihan stok obat yang dialami oeh RSUD dr. Djasamen Saragih Pematangsiantar dapat menyebabkan obat menjadi kadaluwarsa sehingga tidak dapat digunakan (Soraya, Surwanti, & Pribadi, 2022).…”
Section: Pendahuluanunclassified
“…Ketidakstabilan tingkat persediaan yang terjadi mengakibatkan tingginya jumlah biaya penyimpanan dan biaya pemesanan yang harus dikeluarkan olleh perusahaan. Biaya yang dikeluarkan dalam mengadakan persediaan antara lain biaya listrik, biaya karyawan gudang, biaya telepoln, biaya pengiriman, dan biaya bolngkar (Soraya, Surwanti, & Pribadi, 2022). Rumah Tempe Asli HB masih belum efektif dan efisien dalam melakukan pengendalian persediaan sehingga perlu dibantu dengan metolde khusus agar dapat meminimumkan toltal biaya persediaan atau biaya pembeliannya (A. D. Anjani & Berliana, 2019).…”
Section: Pendahuluanunclassified